2017
DOI: 10.48550/arxiv.1701.02906
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Second Order QED Processes in an Intense Electromagnetic Field

Abstract: Some non linear, second order QED processes in the presence of intense plane electromagnetic waves are investigated. Analytic expressions with general kinematics are derived for Compton scattering and e + e − pair production in a circularly polarised external electromagnetic field. Special kinematics, including collinear photons and vanishing external field intensity, are employed to show that the general expressions reduce to expressions obtained in previous work. The differential cross sections were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 123 publications
0
6
0
Order By: Relevance
“…We note though that historically there have been a larger number of papers on 2 → 2 processes, e − e − → e − e − and e − γ → e − γ, following the seminal papers [285,286] which showed that these processes have resonances at the pole of the propagator of the intermediate particle, which gives another example where one has to take higher-order-in-α corrections into account. The literature on these processes is reviewed in [287]. For more recent papers on 2 → 2 processes see [288] and references therein.…”
Section: Second-order Processesmentioning
confidence: 99%
“…We note though that historically there have been a larger number of papers on 2 → 2 processes, e − e − → e − e − and e − γ → e − γ, following the seminal papers [285,286] which showed that these processes have resonances at the pole of the propagator of the intermediate particle, which gives another example where one has to take higher-order-in-α corrections into account. The literature on these processes is reviewed in [287]. For more recent papers on 2 → 2 processes see [288] and references therein.…”
Section: Second-order Processesmentioning
confidence: 99%
“…The presence of the phase derivative Φ (see (17)) in the denominator of ( 19) complicates final state integrations, however, and it would be useful to have a simpler, equivalent expression before proceeding. For pulses with no DC components the regulated expression in (19) is exactly equal to…”
Section: A Regularisation and Gauge Invariancementioning
confidence: 99%
“…(See e.g. [12][13][14][15][16][17][18][19] for other processes.) To our knowledge absorption has not been considered in detail for pulsed laser fields (though for the constant field case see [20], and below).…”
Section: Introductionmentioning
confidence: 99%
“…We note though that historically there have been a larger number of papers on 2 → 2 processes, e − e − → e − e − and e − γ → e − γ , following the seminal papers [295,296] which showed that these processes have resonances at the pole of the propagator of the intermediate particle, which gives another example where one has to take higher-order-in-α corrections into account. The literature on these processes is reviewed in [297]. For more recent papers on 2 → 2 processes see [298] and references therein.…”
Section: Second-order Processesmentioning
confidence: 99%